Journey of Alpinia galanga from kitchen spice to nutraceutical to folk medicine to nanomedicine. (12th June 2022) - Ramanunny, Arya Kadukkattil; Wadhwa, Sheetu; Gulati, Monica; Vishwas, Sukriti; Khursheed, Rubiya; Paudel, Keshav Raj; Gupta, Saurabh; Porwal, Omji; Alshahrani, Saad M.; Jha, Niraj Kumar; Chellappan, Dinesh Kumar; Prasher, Parteek; et al.
Abstract: Ethanopharmacological importance: Alpinia galanga (L.) Willd (AG), belonging to Zingiberaceae family is used as a spice and condiment in various culinary preparations of Indonesia, Thailand and Malaysia. It has been also used as a key ingredient in various traditional systems of medicine for the treatment of throat infection, asthma, urinary ailments, inflammation and rheumatism amongst other conditions. AG is widely used as a functional food and included in various preparations to obtain its nutraceutical and pharmacological benefits of its phytoconstituents such as phenyl propanoids, flavonoids and terpenoids. Over the past decades, several researchers have carried out systematic investigation on various parts of AG. Numerous studies on AG rhizomes have shown positive pharmacological effects such as anti-inflammatory, anticancer, antipsoriasis, antiallergic, neuroprotective and thermogenesis. Till date, no comprehensive review summarizing the exploitation of AG into nanomedicine has been published. Aim of the review: This comprehensive review aims to briefly discuss cultivation methods, propagation techniques, extraction processes for AG. The ethnopharmacological uses and pharmacological activities of AG extracts and its isolates are discussed in detail which may contribute well in further development of novel drug delivery system (NDDS) i.e. future nanomedicine. Materials and methods: Information about AG was collected using search engine tools such as Google, Google Scholar, PubMed, Google Patent, Web of Science and bibliographic databases of previously published peer-reviewed review articles and research works were explored. The obtained data sets were sequentially arranged for better understanding of AG's potential. Results: More advanced genetic engineering techniques have been utilized in cultivation and propagation of AG for obtaining better yield. Extraction, isolation and characterization techniques have reported numerous phytoconstituents which are chemically phenolic compounds (phenyl propanoids, flavonoids, chalcones, lignans) and terpenes. Ethnopharmacological uses and pharmacological activity of AG are explored in numerous ailments, their mechanism of action and its further potential to explore into novel drug delivery system are also highlighted. Conclusions: The review highlights the importance of plant tissue culture in increasing the production of AG plantlets and rhizomes. It was understood from the review that AG and its phytoconstituents possess numerous pharmacological activities and have been explored for the treatment of cancer, microbial infection, gastrointestinal disorders, neuroprotective effects, obesity and skin disorders. However, the use of AG as alternative medicine is limited owing to poor solubility of its bioactive components and their instability. To overcome these challenges, novel drug delivery systems (NDDS) have been utilized and found good success in overcoming its aforementioned challenges. Furthermore, efforts are required towards development of scalable, non-toxic and stable NDDS of AG and/or its bioactives. Graphical abstract: Image 1